PRO DAN KONTRA PASAL TENTANG OUTSORCING DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Samud Samud; Asep Saepullah (IAIN Syekh Nurjati Cirebon, 2020)
Conflicts or disputes can occur in the world of employment where the parties are called workers and employers. Actually conflicts or disputes between workers and employers need not be feared because conflicts can have a positive impact on the parties involved as long as the conflict is not based on a spirit of violence. If the conflict is based on violence it will bring loss and hostility. All this time disputes between workers and employers have often been resolved in anarchic ways such as violent demonstrations, arson, strikes to the closure of companies. Disputes should be resolved peacefully and mutually beneficial. Outsourcing or outsourcing is a system that has been widely used in business entities. Some parties consider that outsourcing efficiency in business processes can be achieved, but for some other parties, outsourcing is considered to be detrimental to workers. Legally, there have been several laws and regulations in Indonesia that accommodate the permissibility of implementing an outsourcing system.